2010
DOI: 10.5581/v33n1a10
|View full text |Cite
|
Sign up to set email alerts
|

Resting blood lactate in individuals with sickle cell disease

Abstract: Resting blood lactate in individuals with sickle cell diseaseBackground: The most common hereditary hemoglobin disorder, affecting 20 million individuals worldwide, is sickle cell disease. The vascular obstruction resulting from the sickling of cells in this disease can produce local hypoxemia, pain crises and infarction in several tissues, including the bones, spleen, kidneys and lungs. Objective: To determine red blood group genes in a Brazilian populations. Methods:The present study is characterized as a ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Cardiorespiratory morbidity of SCA HbSS genotype contributes to functionality decreasing. 25,26 This can be associated with anthropometric variables such as weight and height, which were worse in patients of the SCAG compared with the control group. Some studies have shown that the resting energy expenditure of these patients is up to 20% higher when compared to healthy individuals, this is due to erythropoiesis, increased cardiac work, chronic hemolysis, and hypoxia in tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Cardiorespiratory morbidity of SCA HbSS genotype contributes to functionality decreasing. 25,26 This can be associated with anthropometric variables such as weight and height, which were worse in patients of the SCAG compared with the control group. Some studies have shown that the resting energy expenditure of these patients is up to 20% higher when compared to healthy individuals, this is due to erythropoiesis, increased cardiac work, chronic hemolysis, and hypoxia in tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Proline build-up could be due to increased synthesis or decreased breakdown by the enzymes proline oxidase or proline dehydrogenase (PRODH), respectively. As the level of lactate, an inhibitor of PRODH, is elevated in SCD patients compared to control subjects following a shift towards anaerobic metabolism (Petto et al, 2011), high lactate levels may contribute to the development of albuminuria in SCD via increased proline levels.…”
mentioning
confidence: 99%